The place and role of decrees as sub-normative legal acts in the system of nature protection - Kindyuk, Borys (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article considers the history of the use and development of the decree law in prerevolutionary Russia and the USSR with the aim of protecting natural objects. The reasons for the adoption of the decrees of the Presidium of the Supreme Soviet of the USSR aimed at protecting subsoil resources, fish stocks, land, forests, providing for punishment for violation of hunting rules, as well as calculation of their quantitative indicators are investigated